Nilai Budaya Panji dalam Wayang Topeng Jombang Serta Relevansinya Terhadap Pendidikan Karakter - Amanda, Dila Rizki; Faridah, Faridah; Dalimunthe, Fatimah Azzahra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Character education is currently a central issue in the world of education. Wayang Topeng Jombang, with strong historical roots, offers an interesting alternative to enrich the character learning process. This research examines the cultural values of Panji, which is inherited through Wayang Topeng Jombang, can be a source of inspiration in shaping students' characters. This research uses a qualitative approach with phenomenological methods to explore the deep meaning of Panji's cultural values in Wayang Topeng Jombang. Data were collected through a descriptive qualitative approach. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the Panji values found have significant relevance in the context of character education. The implication of this study is the need to develop an educational program that integrates Wayang Topeng Jombang as a learning medium to instill character values in students.